THU0016 Investigation of RA genetic susceptibility loci contribution to response outcomes following conventional DMARD treatment in early RA. (23rd January 2014) - Morgan, M.D.; Twigg, S.; Hensor, E.M.A.; Conaghan, P.G.; Worthington, J.; Emery, P.; Barrett, J.H.; Morgan, A.W.
Abstract : Background: The first-line treatment of rheumatoid arthritis (RA) involves the introduction of one or more disease-modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) or more historically sulphasalazine (SSA). Many patients only achieve a partial response to these therapies, ultimately requiring biological therapy. There are currently no predictive biomarkers that are sufficiently robust to inform treatment decisions in routine clinical practice. Objectives: To investigate RA genetic susceptibility variants in the context of treatment outcomes in the initial 6 months of conventional DMARD therapy in RA. Methods: Clinical data from early RA patients recruited into a multi-centre observational cohort were used, consisting of matched clinical and genotyping data on 608 patients with 6 month follow-up. A multivariate analysis of each of 41 single nucleotide polymorphisms (SNPs) across 34 genomic loci previously associated with susceptibility to RA were investigated for association with primary and secondary treatment outcomes; the primary outcome of improvement in DAS28 (ΔDAS28; baseline DAS28 minus 6month DAS28) after adjustment for baseline DAS28 and baseline HAQ, and the secondary outcome of achieving a low-disease activity state at 6 months (DAS28≤3.2) adjusted for baseline HAQ only. A threshold for nominal association was set at p<0.05, with a Bonferroni adjusted p<1.47×10 -3 for 34 tests based on the number of loci tested for association. Results: The 608 patients with 6 month follow-up data included in this analysis had a mean age at baseline of 59.4 years (SD 12.9), mean symptom duration of 8.59 months (SD 9.6), (70.7%) were female, 70.8% were seropositive for RF and/or ACPA (RF 70.5%, ACPA 61.4%) and 38.7% achieved a low disease activity state (DAS28≤3.2 at 6months). No differences were observed in treatment outcomes between patients on MTX or SSA (ΔDAS28 p=0.858, DAS28≤3.2 p=0.728). SNPs mapping to the FCGR2A, TRAF1/C5 and UBASH3A loci (rs12746613, rs10760130 and rs3788013 respectively) showed nominal association with ΔDAS28 at 6months follow up (p=0.028, p=0.035, p=0.034, respectively). Two SNPs were found to show nominal association with DAS28≤3.2 at 6months at the STAT4 (rs10181656) and UBASH3A (rs3788013) loci (p=0.004 and p=0.045, respectively). No SNPs were found to be associated with treatment outcomes at the Bonferroni adjusted threshold. Conclusions: Genetic variants associated with modulating susceptibility to RA may also have a role in determining treatment outcomes in early RA patients following conventional DMARD treatment. Replication studies in comparable populations are needed in order to interpret these findings robustly. Disclosure of Interest: None Declared